Detection of Metallo-Beta-Lactamase (MBL) in non-fermenter Gram-negative bacilli using combined disk and MBL-E-strip methods - Gul, Javeria; Javed, Iffat; Mushtaq, Sohaila; Anwar, Muhammad Saeed (Journal of Fatima Jinnah Medical University, 2019)
Background: The occurrence and spread of antibiotic resistant bacteria is one of the highest challenges, especially for developing countries. The rate of resistance among Gram-negative bacteria especially non-fermenters are increasing to all available antibiotics. One major concern is their resistance to the beta lactam antimicrobials. The aim of this study was to evaluate the effectiveness of combined disc method in comparison with MBL-E-strip method for the detection of Metallo-Beta-Lactamase (MBL) producing non-fermenter Gram-negative bacilli. Materials and methods: In this study non-fermenter Gram-negative bacilli were isolated from different clinical specimens including blood, pus, urine, fluid aspirates and respiratory tract. Isolates were identified up to species level by API 20 NE kit. Antimicrobial susceptibility testing of non-fermenter Gram-negative organisms were achieved by modified Kirby Bauer disk diffusion method as recommended in Clinical and Laboratory Standards Institute (CLSI) guidelines for Antimicrobial Susceptibility Testing (M100-S28). Combined disc test and Metallo-Beta-Lactamase E-test strips were used for the detection of Metallo-Beta-Lactamases. Results: Out of a total number of 51 isolates (non-fermenter Gram negative bacilli) which were resistant to imipenem were included in this study. Among total, 16 were Acinetobacter baumanii, 16 were Burkholderia cepacia, 7 were Pseudomonas aeruginosa, 5 were Pseudomonas luteola, 4 were Stenotrophomanas maltophilia, 2 were Pseudomonas fluorescens and 1 was Pseudomonas stutzeri. The comparison of two phenotypic methods showed that the combined disk test (CDT) detected MBL production in 80.3% isolates, whereas MBL-E- strip detected MBL production in 90.2%. The diagnostic accuracy of CDT was 78% in this study. Conclusions: Combined disc test and MBL-E-strip tests have reliable sensitivity and specificity and were comparable for detection of MBL enzyme. CDT has 83% sensitivity and 40% specificity. The high sensitivity indicates that this test can be used as a good screening tool for MBL detection. These results can help to detect MBL production more effectively and efficiently.